Effect of skill-based training vs. small-sided games on physical performance improvement in young soccer players - Karahan, M. (Biology of Sport, 2020)
Recently, there has been increasing attention to research related to the effect of skill-based or game-based training on soccer players` physical performance. Therefore, this study aimed to compare the effectiveness of skill-based training (SBT) at maximum intensity versus the small-sided game (SSG) on the physical performance characteristics of young soccer players during the pre-season period. Twenty-two male soccer players (mean age 15.3 ± 3 years) were randomly assigned to either an SBT or SSG fully controlled intervention programme, running parallel for eight weeks and held twice a week. On three non-consecutive days before and after training players completed a test battery consisting of the 20 m sprint, T-run, countermovement jump, running anaerobic sprint test (RAST) and 20 m shuttle run. Data were analysed with a two-way ANOVA test for repeated measures. SBT and SSG interventions induced a significant improvement in the anaerobic power (10.9% vs 6.2%), explosive power (8.5% vs 5.6%), VO2max (6.7% vs 6.5%) and vertical jump (5.3% vs 2.9%), respectively. When the improvements in the physical performance variables of both groups are compared, the SBT group achieved greater improvement than the SSG group in anaerobic power (by 4.7%), in explosive power (by 2.8%), in vertical jumping (by 2.3%), in the 20 m sprint (by 2.2%) and T-test scores (by 1.7%). However, improvements in the VO2max were similar in both groups. The results of the present study suggest that SBT at maximum intensity may be more effective than SSG in improving the physical performance characteristics of young soccer players in the pre-competitive season.